Kewenangan Dan Struktur Hubungan Hukum Antara Dewan Penjamin Simpanan Dengan Perbankan - Tarantang, Jefry; Kurniawan, Rahmad; Pelu, Ibnu Elmi A. S.; Marcelia, Baiq Wira Dharma Dhea Tri (IAHN Tampung Penyang Palangka Raya, 2023)
According to the banking law, a bank can have its business license revoked and be liquidated. In the bank dissolution system, the Deposit Insurance Corporation is very influential when it comes to handling bank customer capital returns. The granting of these powers and privileges is expected to increase the rate of recovery for the Store Protection Partnership, thereby maintaining the suitability of the store protection program. The emergence of Law No. 24 of 2004 concerning the Deposit Insurance Corporation represents another part of the public finance framework. The presence of the Deposit Insurance Corporation cannot be separated from efforts to develop security in the financial area and will rebuild public confidence in the financial sector. This assessment focuses on the performance and ability of the Deposit Insurance Company in fulfilling its obligations to hold, protect, and submit legal decisions to the people as bank users in the dissolution of banks based on financial regulations.